Evaluation of Occupational Safety and Health Requirements in Confined Space at Turbine Maintenance PT. Sinergi Nusantara Gula PG Tjoekir - Lilis Hindun Wahyuni; Merry Sunaryo; Muslikha Nourma Rhomadhoni; Friska Ayu (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
Confined space is a high-risk workplace because it contains various sources of danger such as toxic gases, lack of oxygen, and fire risk. PT. Sinergi Gula Nusantara PG Tjoekir has implemented work procedures based on BINWASNAKER No. 113/DJPPK/XI/2006, but evaluation is needed to ensure compliance with the latest regulations, namely Permenaker No. 11 of 2023. The study aimed to evaluate the OSH Requirements in confined space turbine maintenance at PT. SGN PG Tjoekir is by Permenaker no. 11 of 2023, including confined space classification, access restrictions to enter confined spaces, entry permits, safe work procedures, equipment and equipment, and OSH confined space personnel. The type of research method used is qualitative descriptive, namely providing an overview of OSH requirements in a limited space for turbine maintenance. Then the data obtained is compared to its conformity with Permenaker No. 11 of 2023. The results of this study out of 17 conditions that must be met only 60% that have been met. The conditions that have not been met are the classification of confined space, testing and monitoring of hazardous atmospheric gases, labeling and energy isolation forms, supply respirators, testing, and monitoring equipment for hazardous atmospheric gases, penetrating voltage measuring instruments, and OSH confined space personnel. This study concludes that the OSH requirements in confined space turbine maintenance are in the category of lacking. The advice provided by the company can update the entry permit procedure and increase compliance with the latest regulation, namely Permenaker No. 11 of 2023 to improve work safety.